A MATHEMATICAL MODEL FOR DELIVERY ZONE GROUPS BASED ON COURIER ASSIGNMENT OPTIMIZATION: A CASE STUDY IN A LOGISTICS SERVICE PROVIDER - V. Reza Bayu Kurniawan; Fransiska Hernina Puspitasari (Spektrum Industri, 2020)
Logistics service providers are the key stakeholder in Indonesian logistics activities that are growing significantly and face many challenges. In this research, a case study on a logistics service provider located in the city of Yogyakarta Indonesia is evaluated. The provider is currently experiencing rapid growth indicated by increasing delivery volume and scopes. However, optimal resource management has not been able to be adequately calculated, such as inefficient courier assignment and overloaded couriers' volume. Thus, this study aims to minimize total distances through optimal zone groups under several restrictions. An optimization approach is selected in this research by initially building a mathematical model using a standard form of linear programming. Then, the mathematical model is solved to generate minimum distances. The result indicated that the total minimum distances had been reached with considerable changes in delivery zone grouping, and the couriers' capacity was optimally utilized without overloaded capacity. These zone groups can be used as a reference for further research by taking into account some restrictions such as packages fluctuations as well as adding objective to minimize couriers' traveling time.